2018
DOI: 10.3897/oneeco.3.e28143
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of bumblebees across Europe

Abstract: Insect pollinators are a key component of biodiversity; they also play a major role in the reproduction of many species of wild plants and crops. It is widely acknowledged that insect pollinators are threatened by many environmental pressures, mostly of anthropogenic nature. Their decline is a global phenomenon. A better understanding of their distribution can help their monitoring and ultimately facilitate conservation actions. Since we only have partial knowledge of where pollinator speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 25 publications
0
31
0
Order By: Relevance
“…Bumblebees represent an ideal study species to test this hypothesis. There are considerable long‐term occurrence records available and, as a group, bumblebees have shown declines at the European scale (Biesmeijer et al., 2006; Carvalheiro et al., 2013; Kerr et al., 2015; Nieto et al, 2014; Polce et al., 2018; Rasmont et al., 2005). Previous research has shown that climate change alone is expected to have strong negative impacts for bumblebees at the European level (Rasmont et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Bumblebees represent an ideal study species to test this hypothesis. There are considerable long‐term occurrence records available and, as a group, bumblebees have shown declines at the European scale (Biesmeijer et al., 2006; Carvalheiro et al., 2013; Kerr et al., 2015; Nieto et al, 2014; Polce et al., 2018; Rasmont et al., 2005). Previous research has shown that climate change alone is expected to have strong negative impacts for bumblebees at the European level (Rasmont et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Overview of the analysis. MaxEnt models from Polce et al (2018) are adjusted through the exchange of land‐related predictor variables based on IAP2 land use and projected to 2050 and 2080 under various combinations of climate (WorldClim v1.4 RCP scenarios) and land‐use change (IMPRESSIONS RCP‐SSP core scenarios; Table 1). Net habitat changes per species are calculated as the difference between suitable habitat area in the future maps and suitable habitat area in the baseline map (based on mapped IAP2 land use for around 2010 and climate 1991–2012).…”
Section: Methodsmentioning
confidence: 99%
“…The distribution maps indicate for each species (1) the probability of occurrence and (2) presence/absence at a spatial resolution of 10 x 10 km, based on a maximum entropy (MaxEnt) modeling approach (Phillips et al, 2006) that establishes a functional relationship between species occurrence and 22 environmental predictor variables (Tables 2 and 3). Species occurrence data for the years 1991–2012 underlying the MaxEnt models originate from the Atlas Hymenoptera (Rasmont & Francis, 2018) and consisted of validated presence‐only bumblebee records, gathered from different data donors in Europe (see Rasmont et al, 2015 and Supplementary Material 7 in Polce et al, 2018 for further details), collated during the ‘Status and trends of European pollinators’ project (Potts et al, 2015). The environmental predictors were based on CORINE land cover for the year 2006 for land‐related variables (Bossard et al, 2000), ‘E‐OBS’ gridded meteorological data for bioclimatic variables (Cornes et al, 2018), and the ‘EU‐DEM’ for topography (EEA, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spatially referenced distribution data were extracted from Polce et al. (2018) with the addition of new original data held in the database hosted at the University of Mons (http://www.atlashymenoptera.net/page.aspx?id=169). This data set consists in occurrence data accumulated from published literature, as well as from bumblebee collections deposited in museums and universities.…”
Section: Methodsmentioning
confidence: 99%